The Effect of Plant Spacing on Some Quality Traits of Fodder Beet (Betavulgaris var. Crassa) Varieties - Al-Jbawi, Entessar; Bagdadr, Mohammad; Nemr, Yousef (International Journal of Environment, 2014)
A field experiment was conducted in the (2011/12) season to study the effect plant spacing on yields and its components of four fodder beet cultivars. The experiment was a randomized complete block design (RCBD) in split plots arrangement with three replicates, plant spacing (25X60, 20X60 and 25X50 cm) were assigned to the main plots and fodder beet cultivars (Jamon, Splendids, Starmon and Vermon) were allotted to the sub plots. Spacing had a significant effect on all the quality traits except protein content of shoot. Spacing and varieties exhibited highly significant (p<0.01) differences in all of the studied characteristics. Varieties affected dry matter content of root, and protein content of shoot and root significantly (p<0.05). Dry matter content of shoot, Ash content of shoot and root, and organic content of shoot and root were not significantly affected by varieties. Vermon sown at 25 cm apart and 60 cm between rows significantly (p<0.05) attained the highest quality traits. DOI: http://dx.doi.org/10.3126/ije.v3i3.11089 International Journal of Environment Vol.3(3) 2014: 286-293